Station blackout mitigation strategies analysis for Maanshan PWR plant using TRACE. (March 2016) - Lin, Hao-Tzu; Wang, Jong-Rong; Huang, Kai-Chun; Shih, Chunkuan; Chiang, Show-Chyuan; Liu, Chia-Chuan
Highlights: A TRACE 5.0 p4 model for Maanshan NPP (PWR) has been developed. The parameters responses of Maanshan NPP TRACE model are consistent with startup tests and FSAR data. The results of TRACE show good agreement with Maanshan NPP SBO accident data. Maanshan NPP TRACE model is used to study the mitigation strategies for SBO. Abstract: Maanshan nuclear power plant (NPP) is a two-unit Westinghouse three-loop PWR NPP. This research focuses on the analysis and simulation of Maanshan NPP station blackout (SBO) accident that happened on 18th March, 2001, and thermal–hydraulic phenomena of the plant during SBO with and without mitigation strategies. There are two main steps in this study. The first step was the establishment of Maanshan NPP SNAP/TRACE models. These models were tested and the results of TRACE were compared with the startup test and FSAR data. Analysis results indicate that Maanshan NPP SNAP/TRACE models predict not only the behaviors of important plant parameters consistently with the startup test and FSAR data, but also their associated numerical values with respectable accuracy. The next step was the SBO accident simulation and analysis of Maanshan NPP SNAP/TRACE model. The results of TRACE show good agreement with the plant data. Several mitigation strategies were simulated and studied by using this model in this research.